Sponsored links: Algebra eBooks
 

Related

Solution

? dotproduc;

Calculate

Solution

f(x1,X2):=((x1)^2 - (...

Calculate

Solution

A_xm_t0:(Mwi_x[t]-Mwi...

A_xm_t1:(Mwa_x[t]-Mwa...

eq:A_xm_t0=Cwi_x[t]/D...

Calculate

Solution

-27*p2+54*p16+54*p2 -...

Calculate

Solution

f:2*x^2*x;

derive([f]);

Calculate

Solution

1*3^-1+2*3^-2+1*3^-3;

Calculate

Solution

A:matrix[[-3,1,0],[2,...

B:matrix[[2,-1,3],[1,...

C:matrix[[-1,2,1],[1,...

Calculate

Solution

(S * usd_df / brl_df ...

Calculate

-1

Run Example
(%i1)f: b and (not a or c ) or a and not b and not c and not d ;
(%o1)  (b and ((not a) or c)) or (a and (not b) and (not c) and (not d))
(%i2) f,a=false,b=true,c=false,d=false;
(%o2)                                true
(%i3) 
Run Example
a:(-c_y + s_y)*cs_x + (c_x + s_x)*cs_y + (c_y - s_y)*s_x - (c_x - s_x)*s_y = 0;
(%o1) cs_x (s_y - c_y) + (s_x - c_x) s_y + s_x (c_y - s_y)
                                                         + cs_y (s_x + c_x) = 0
(%i2) b:((s_x - b_x)^2 + (s_y - b_y)^2) = ((s_x - cs_x)^2 + (s_y - cs_y)^2);
                     2              2               2               2
(%o2)     (s_y - b_y)  + (s_x - b_x)  = (s_y - cs_y)  + (s_x - cs_x)
(%i3) 
Run Example
Solve(((0.453-x)/(1-x)^0.453)=1);
                                   0.453 - x
(%o1)                       Solve(------------ = 1)
                                         0.453
                                  (1 - x)
(%i2) 

Related Help

Help for -1